Light-dependent absorption and selective scattering changes at 518 nm in chloroplast thylakoid membranes. - Thorne, S W (1975)
The light-induced absorbance change at 518 nm of isolated chloroplasts consists of a rapid phase, and a slow phase which is complete in about 20 sec. The slow component of the 518 nm absorbance change correlates with the light-induced change in 90 degrees light scattering at 518 nm. Both show a similar time course, similar pH dependence with a maximum at pH 6.0, and similar sensitivity to inhibitors and to treatment of the chloroplasts with a low concentration of glutaraldehyde. Their light minus dark difference spectra are similar with maxima at about 520 nm. It is concluded that they are manifestations of the same phenomenon, and the slow absorbance increase at 518 nm is due to enhanced scattering. It is proposed that the light-induced changes in scattering at 518 nm reflect alterations in selective dispersion, due to proton uptake and conformational changes in the chloroplast thylakoid membrane.